Production technology of poultry sausage-1: the studies on the quality of chemical, microbiological and organoleptic - Nazif Anıl; Yusuf Doğruer; Ümit Gürbüz; Semra Kayaardı; Abdullah Keleş (Eurasian Journal of Veterinary Sciences)
This study was carried out for producing a new product "Poultry Sausage" and investigate its quality factors.The poultry sausage used in the experiments was developped by the applications of several tests and trials. Besides the various formulas and technological methods have been used, also the effects of several factors such as tempareture, moisture and duration were also investigated. The poultry sausage samples developped by mixing chicken meat, beef and soybean flour in certain percentages (designed in groups) were examined from the chemical, microbiological and organoleptic point of view. All the samples were analysed at various stages of aging (1st, 3rd and 7th) and storage (14th, 21st and 30th) days significant differences were determined in chemical composition of poultry sausage according to the stages of aging and storage. At first day, moisture, protein and fat contents and acidity values showed differences. At 3rd day only value of acidity, at 7th day moisture, ashand water activity (aw) values, at 14th day fat ash, salt and aw values, at 21st day moisture, protein, fat, ash and salt contents and value of pH and finally at 30th protein, fat and salt contents of sausage among the groups showed significant differences. There was no significant differnce in mikroflora between the groups in both aging and storage. Although the group C3 differed from the other groups in the number of Staphylococcus - micrococcus microorganisms at the begining stage of aging. It was detected that the number of total microorganisms and Lactobacillus species increased among aging and storage while coliform bacteria and yeasts-moulds showed significant and Staphylococcus - micrococcus species showed slight decreasing. After 7th day coliform bacteria was not detected. It was determined that the groups of C2 and C3 (consisting of chicken meat and beef) were more preferable in organoleptically, The groups B1 and B2 which were consisting of chicken meat beef and soybean flour, were detected poor in organoleptic determination. As a result it was concluded that poultry sausage might be a suitable product, producing by mixing chicken meat and beef especially using reformed chicken.